Implementation of Islamic Educational Values in The Formation of Noble Morals through Extracurricular Activity - Sulasno,; Sumardjoko, Bambang; Fuadi, Djalal (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This study aims to describe the implementation of the Tapak Suci and Japanese language extracurricular activities at SMK Muhammadiyah 1 Sukoharjo in developing students' noble character. This research used a qualitative method with a case study approach. The informants included the principal, the Tapak Suci and Japanese language extracurricular teachers, and the students participating in both activities. Data collection techniques included observation, semi-structured interviews, and documentation. Data were analyzed using an interactive analysis model that encompasses data reduction, data presentation, and conclusion drawing. The results show that the Tapak Suci extracurricular activities contribute to instilling religious character, discipline, responsibility, hard work, creativity, and caring through physical exercise and Islamic values. Meanwhile, the Japanese language extracurricular activities shape these characters through contextual and culturally oriented learning methods. The implications of this research demonstrate the importance of character building through a participatory, contextual, and comprehensive non-formal approach within the educational environment. The results are to serve as a reference for schools in creating extracurricular activities that effectively and relevantly develop student character in response to current demands.